Measuremment of magnetorheological elastomer properties - Suthan A / l Gobi Nathan (2023)
Magneto Rheological Elastomer is a novel class material comprises of elastomeric matrix mixed with ferromagnetic particles. It exhibits adjustable mechanical properties with presence of external magnetic field, in a reversible manner. In contrast to the Magneto Rheological fluids MRE solves the issue arises in MR fluids such as sedimentation of iron particle and formation of hard cake. The project concentrates on identifying the characteristic of MRE under compression test for both isotropic and anisotropic MRE with different volume percentage of carbonyl iron powder. Isotropic and anisotropic MRE with 5%,10% and 20% volume percentage of CIP were fabricated using reliable process. The compression test was conducted with and without magnetic field to both isotropic and anisotropic on Zwick Machine. Neodymium magnets were used to create magnetic field across the MRE. The MRE were compressed up to maximum 25% shear strain with 10mm/min compression rate. The Young Modulus were used to analyze the characteristic of MRE under compression testing. The results obtained shows that anisotropic MRE is stiffer than isotropic MRE. Moreover, increase in iron particle volume percentage in MRE contributes to significant effect on Young Modulus in presence and absence of magnetic field.